Pengolahan Sampah dengan Teknik 3R bagi Pelestarian Lingkungan di Desa Asir-Asir, Kabupaten Aceh Tengah - Ira Zulfa; Eliyin Eliyin; Hajar Ashwad; Firmasyah Firmasyah (Jurnal Pengabdian Masyarakat Waradin, 2025)
A strategic effort to increase community awareness about environmental sustainability was carried out in Asir-Asir Village, Aceh Tengah District through the application of the 3R technique (Reduction, Use, and Transfer). The 3R principle is expected to improve environmental sustainability and reduce waste volume. Asir-Asir Village faces a major problem in waste management, which has a negative impact on public health and the environment. The 3R method offers an effective solution to this problem. Increase community awareness of the importance of good waste management. Reducing waste volume through reduction, reuse and recycling. Community and training on the 3R principles. Create a working group focused on waste management at the village level. The 3R method can be applied in people's daily lives. Transforming the village environment into a cleaner and healthier Asir-Asir: Waste management using the 3Rs technique improves the quality of life of the community and protects the environment.